Differences in dental and oral hygiene status between orthodontic and conventional toothbrush users in fixed orthodontic treatment: Perbedaan status kebersihan gigi dan mulut antara pengguna sikat gigi ortodonti dan konvensional pada perawatan ortodonti cekat - Eddy Heriyanto Habar; Nyili Timo (Makassar Dental Journal PDGI Makassar, 2022)
Good oral and dental hygiene is a challenge for orthodontic patients because food is easily trapped around brackets and under the arches of braces, thus becoming a barrier to brushing teeth. An effective way to get rid of plaque is to use a toothbrush regularly, to keep your teeth and mouth clean and healthy. This study was intended to determine the difference in dental and oral hygiene status between orthodontic and conventional toothbrush users in fixed orthodontic treatment.The results of the analysis of 6 articles are that the use of orthodontic toothbrushes is more effective than conventional toothbrushes in removing plaque. Or-thodontic toothbrushes can also provide a significant plaque reduction effect on fixed orthodontic appliance users. Orthodontic toothbrushes did not show any difference in removing plaque compared to conventional toothbrushes. It was concluded that there were differences in dental and oral hygiene status between orthodontic and conventional brush users in fixed orthodontic treatment.